Kaji Pemanfaatan Atap Sebagai Pemanas Pada Sistem Pengering Bawang Merah (Allium Ascalonicum L.) - Ahmad Syuhada; Ratna Sary; Arie Hantama Siregar (Jurnal Teknik Mesin Unsyiah, 2020)
Allium Ascalonicum L. are one of the agricultural commodities that grow in Aceh that can bear fruits throughout the year. In 2017, the total productive land area reached 725 hectares (HA) with a total production of around 5,739 tons per year. The average of the harvested Allium Ascalonicum L has high levels of water in range of 90 – 92 %, it is necessary to do a better process of drying / storing Allium Ascalonicum L according to SNI 01-3159-1992. This study aims to determine the effect of heating with four variations of flat plate type roofs (iron, aluminum, zinc, iron coated iron sand) so as to increase the rate of heat transfer in the drying chamber. Data is collected at the absorber, heater output, pipe exit, and onion drying / storage chamber. Heaters with an iron roof type are those that best distribute the pipe output temperature of 63 0C and room temperature of 42.6 oC. The type of iron roof has a material shrinkage of 10.8%, the type of iron roof coated with iron sand has a material shrinkage of 10.5%, the type of zinc roof has a material shrinkage of 10%, the type of aluminum roof has a material shrinkage of 7.8%. The highest room humidity was achieved in the aluminum roof type by 78% and the lowest in the iron roof type was 40%.